Rights-Based Justifications for Self-Defense: Defending a Modified Unjust Threat Account - Ford, Shannon Brandt (Philosophy Documentation Center, 2022)
I defend a modified rights-based unjust threat account for morally justified killing in self-defense. Rights-based moral justifications for killing in self-defense presume that human beings have a right to defend themselves from unjust threats. An unjust threat account of self-defense says that this right is derived from an agent’s moral obligation to not pose a deadly threat to the defender. The failure to keep this moral obligation creates the moral asymmetry necessary to justify a defender killing the unjust threat in self-defense. I argue that the other rights-based approaches explored here are unfair to the defender because they require her to prove moral fault in the threat. But then I suggest that the unjust threat account should be modified so that where the threat is non-culpable or only partially culpable, the defender should seek to share the cost and risk with the threat in order for both parties to survive.